A rare cause of pulmonary hemorrhage in the intraoperative period - Anurakti Dev Singla; Anil Sivadasan Radha; Girish Warrier; Meena Trehan (Wolters Kluwer Medknow Publications, 2020)
The perioperative morbidity and mortality in pediatric cardiac surgery can be due to a multitude of factors. Timely identification of the problem helps in altering the treatment strategy and improving the outcome.